Fas and Fas ligand expression in cystic fibrosis airway epithelium. Issue 12 (1st December 1999) - Durieu, Isabelle; Amsellem, Carole; Paulin, Christian; Chambe, Marie-Thérèse; Bienvenu, Jacques; Bellon, Gabriel; Pacheco, Y
Abstract : BACKGROUND: Cystic fibrosis (CF) is a genetic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene and defective expression of CFTR protein in epithelial cells. The main cause of mortality in CF is linked to chronic inflammatory and infectious airway processes. Recent studies have suggested perturbations in the apoptotic process in CF cell lines and enterocytes. A study was undertaken to investigate the expression of Fas and Fas ligand (FasL) in CF bronchial epithelium and CF tracheal cell lines. METHODS: Immunohistochemical staining for Fas (alkaline phosphatase anti-alkaline phosphatase) and FasL (immunoperoxidase) was performed in eight CF bronchial epithelial samples and four controls and immunohistochemical DNA fragmentation (TUNEL) was carried out in four CF patients and four controls. Immunofluorescence staining and flow cytometric analysis of Fas and FasL expression was performed in two human tracheal epithelial cell lines (HTEC) with normal and CF genotype. The dosage of serum soluble FasL was examined in 21 patients with CF and 14 healthy volunteers. RESULTS: FasL expression was markedly increased in patients with CF in both the ciliated and submucosal glandular bronchial epithelium compared with controls; Fas was similarly expressed in bronchial samples from controls and CF patients in both the ciliated epithelium and submucosal glands. High levels of DNA fragmentation were observed in CF but with some epithelial cell alterations. Serum concentrations of soluble FasL were frequently undetectable in patients with CF. In vitro, HTEC expressed Fas and FasL in both genotypes. A higher mean fluorescence intensity for FasL expression was noted in CF genotype HTEC with median (range) for six experiments of 74 (25–101) for CF cells and 42 (21–70) for non-CF cells. CONCLUSION: Fas/FasL interaction is probably implicated in the human CF airway apoptotic pathway. The mechanisms of induction of FasL expression and its role in inducing tissue damage or remodelling or in controlling local inflammatory cell apoptosis remain to be determined.